2003
DOI: 10.1002/zaac.200300128
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Nitride Films Formed by Rapid Thermal Processing (RTP): Depth Profiles and Interface Reactions Studied by Complementary Analytical Techniques

Abstract: The nitridation of vanadium films in molecular nitrogen and ammonia using a RTP‐system was investigated. The V films were deposited on silicon substrates covered by 100 nm thermal SiO2. For a few experiments sapphire substrates were used. Nitride formation at high temperatures (900 and 1100 °C) and interface reactions and diffusion of oxygen out of the SiO2‐layer into the metal lattice at moderate temperatures (600 and 700 °C) were studied. For characterisation complementary analytical methods were used: X‐ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It is found that transition metal nitrides combine the characteristics of both ceramics and metals [1], So they exhibit many attractive properties, such as great abrasion and corrosion resistance, extreme hardness, high melting point, good electric and thermal conductivity, and interesting optical, electronic and magnetic properties [1][2][3]. Besides, vanadium nitride is a superconductor with a transition temperature Tc ranging from 2 to 9 K depending on the nitrogen content [4], and has good catalytic activities to NH 3 synthesis and decomposition, and n-butane dehydrogenation [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…It is found that transition metal nitrides combine the characteristics of both ceramics and metals [1], So they exhibit many attractive properties, such as great abrasion and corrosion resistance, extreme hardness, high melting point, good electric and thermal conductivity, and interesting optical, electronic and magnetic properties [1][2][3]. Besides, vanadium nitride is a superconductor with a transition temperature Tc ranging from 2 to 9 K depending on the nitrogen content [4], and has good catalytic activities to NH 3 synthesis and decomposition, and n-butane dehydrogenation [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, these materials present unique physical and chemical traits, which greatly increase their importance in practical applications and fundamental studies, such as for example, their use as raw materials in cutting tools resistant to wear and corrosion. 2,4 Furthermore, since Levy and Boudart, 5 in the 1970s, discovered that tungsten carbide (WC) possesses special catalytic properties, and, from a qualitative point of view electronic properties analogous to those of noble metals, the interest in their electronic and magnetic properties 1 has been greatly on the increase.…”
Section: Introductionmentioning
confidence: 99%
“…The heat treatment is a critical step in the preparation of these materials from the precursors; therefore, a careful study of the heat treatment would help to clarify the relation between the preparation method and the properties of these materials. Some methods employed recently to synthesize VN are rapid thermal processing [10], thermal reduction/nitration in an autoclave at 500…”
Section: Introductionmentioning
confidence: 99%